Performance of sheep grazing Brachiaria decumbens, Panicum maximum and Pennisetum purpureum in Gliricidia sepium alley plots - Osakwe I.I. (Advanced nutrition and feeding strategies to improve sheep and goat, 2007)
The introduction of forage legumes into pastures has generally improved animal productivity from grasses by increasing total edible biomass. Tree foliages have essentially the same role in the nutrition of ruminants as legume forage. In addition, trees are deep rooted, which allows them to grow often well into the dry season, whereas forage legumes are often shallow rooted and may dry off during dry seasons. It was against this background that an experiment was designed to study performance of sheep grazing Brachiaria decumbens, Panicum maximum and Pennisetum purpureum in Gliricidia sepium alley plots. Twelve paddocks of approximately 0.03 ha containing Gliricidia sepium alley planted in rows 4 m apart and interplanted with 4 rows of either Brachiaria decumbens, Panicum maximum, or Pennisetum purpureum were each grazed by 3 sheep. The three grass combinations within the alley plots were replicated four times. The animals grazed continuously for 28 days in the sub plots. Sheep grazing the Gliricidia/Panicum plot had a higher (P<0.01) growth rate (38 g/d) than those animals grazing both the Gliricidia/Bracharia (23 g/d) and Gliricidia/Pennisetum (21 g/d) plots respectively. There was no difference between sheep grazing the Gliricidia/Bracharia and Gliricidia/Pennisetum plots. The total dry matter intake of sheep on the Gliricidia/Panicum plot was higher (P<0.05) (1.33 kg DM/d) than that of sheep on Gliricidia/Bracharia (0.86 kg DM/d) and Gliricidia/Pennisetum (0.43 kg DM/d) plots respectively. The total biomass from the Gliricidia/Bracharia (23 t/ha) and Gliricidia/Panicum (21 t/ha) plots respectively were higher (P<0.01) than the total biomass from the Gliricidia/Pennisetum (13 t/ha) plot. These results demonstrate that grazing West African dwarf sheep in a Gliricidia sepium/Panicum maximum plot improved their growth rate during dry periods when feed supplies are limited. It also underscores the poor performance of animals grazing
11. Seminar of the FAO-CIHEAM Sub-Network on Sheep and Goat Nutrition, 2005/09/08-10, Catania (Italy)